2018
DOI: 10.1111/acel.12890
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐free DNA as a biomarker of aging

Abstract: Cell‐free DNA (cfDNA) is present in the circulating plasma and other body fluids and is known to originate mainly from apoptotic cells. Here, we provide the first in vivo evidence of global and local chromatin changes in human aging by analyzing cfDNA from the blood of individuals of different age groups. Our results show that nucleosome signals inferred from cfDNA are consistent with the redistribution of heterochromatin observed in cellular senescence and aging in other model systems. In addition, we detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 65 publications
4
83
2
1
Order By: Relevance
“…Recently, growing evidence shows that TERT is protective in the microcirculation against prolonged vascular stress [7,8]. Among the different biomarkers proposed, including cell-free DNA and circulating extracellular RNAs [9,10], growth differentiation factor (GDF-15) appears particularly promising due to the ease of collecting specimens and the low costs. However, little is known about how serum GDF-15 changes with age.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, growing evidence shows that TERT is protective in the microcirculation against prolonged vascular stress [7,8]. Among the different biomarkers proposed, including cell-free DNA and circulating extracellular RNAs [9,10], growth differentiation factor (GDF-15) appears particularly promising due to the ease of collecting specimens and the low costs. However, little is known about how serum GDF-15 changes with age.…”
Section: Introductionmentioning
confidence: 99%
“…However, the distribution of fragment length in stroke patients is still unclear. Recently, researchers had revealed that the distribution of nucleosome spacing displayed regularity in the healthy group, whereas aberrant nucleosome spacing could be detected in many diseases [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Teo et al showed a remarkable consistency between nucleosome signals of cfDNA and redistribution of heterochromatin, which has a role in cellular senescence and aging. In this perspective, cfDNA may be designated as a biomarker of age or a predictor of health status (14).…”
Section: Discussionmentioning
confidence: 99%